Resilience Turn in German Development Strategy and Humanitarian Intervention - Jonathan Joseph (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2017)
Resilience has emerged as a key theme in recent policy making. It spans a range of policy fields from infrastructure protection through to humanitarian intervention. This Research Paper looks at resilience as a theme of development strategy and humanitarian intervention and examines how it has emerged in German policy making. It argues that the dominant approach to resilience is a form of neoliberal governmentality that seeks to govern populations from a distance, devolve responsibility to people and communities, promote market mechanisms, encourage entrepreneurial behaviour and promote adaptation innovation and transformation among traditional communities. However, it is also recognised that this is a strongly Anglo-Saxon approach, targeted at specific individuals and communities. The purpose of the paper is to consider the extent to which German policy making is simply a reflection of this dominant Anglo-Saxon approach, or whether there is a more distinctive German view of resilience. It does this by exploring tensions in the German discourse, indicating that there might be other political dynamics in play alongside the neoliberal ones.
urn:nbn:de:hbz:464-20180111-125820-8
Keywords: 320; Resilience; development; aid; policy; humanitarian; international relations; global development